Desenvolvimento do core set da Classificação Internacional de Funcionalidade, Incapacidade e Saúde (CIF) para hanseníase – etapa do estudo clínico quantitativo e qualitativo - Carregosa, Elisvânia Barroso (2017)
Leprosy it mainly affects the skin and the peripheral nervous system, causes multiple deformities and body disfigurations, interfering directly in the individual’s personal and professional life. The International Classification of Functioning, Disability and Health (ICF) is an instrument that classifies and assists to describe function and disability related to health conditions, reflecting a new approach to identify dysfunctions, classifying them in the biological, individual and social context. The objective of this study is to identify, through a clinical study, the main dysfunctions presented in cases of leprosy and thus to select categories to develop the core set of the ICF for leprosy. The type of this study is clinical descriptive, cross-sectional with quantitative and qualitative analysis. The sample was composed of patients with leprosy, who were recruited at the Centers of leprosy in Sergipe. For data collection with the quantitative approach, validated and standardized functional evaluations were used that represented each ICF domain. In the data collection of the qualitative approach, a structured, standardized questionnaire developed by WHO was used. The data were recorded in Office 2010 program to calculate means, frequencies and percentages. The dysfunctions prevalent in at least 5% of the participating volunteers were selected to be extracted the categories of the ICF with their respective codes to compose the core set. Participants in this study were 29 patients with leprosy. The mean age of the participants was 44.9 (± 13.72), predominance of 60% men. In the study with a quantitative approach, the most relevant functional disabilities were in the body structure domain, where "Structures of areas of skin - s810" was the most prevalent with 78%, in the body function domain the most representative category were "Touch function - b265" with 100% prevalence of participants who presented deficits in sensory. In the field of activity and participation the category: “Carrying, moving and handling objects - d430” had 100% of the participants with limitations. In the area related to participation the category: “Recreation and Leisure - d920”, 89% of the participants had restriction to participate. Regarding environmental impact, the category "Health services, systems and policies - e580" represented a barrier to 56% of participants. Different from what was found in the quantitative study, the results collected in the qualitative study demonstrated a greater number of categories in the environmental factors domain. However, when the amount of categories in the two studies were compared considering the total number of categories of the ICF, with the relative frequency of categories, we observed that the environmental domain is the “incapacity” most prevalent in both studies with the quantitative and qualitative approach. The ICF categories in each domain found in the quantitative study and the qualitative study help to map the functional disabilities of patients with leprosy.